DEVELOPMENT OF MODEL OF INFRASTRUCTURE ENSURING SMALL AND AVERAGE BUSINESS IN THE REGION - V. Dobroconny; I. Kohanovsky (Вестник университета, 2018)
The basic mechanisms of infrastructure support and state support of entrepreneurship are considered. At the present stage, one of the accents in the development of the economy of the Russian Federation is on the development of small business, the development of small and medium-sized business acquires special importance in the conditions of imposing sanctions against Russia. Based on the analysis of infrastructure support mechanisms, a model of infrastructure provision for small and medium-sized enterprises at the regional level (on the example of the city of St. Petersburg) has been proposed.